2008
DOI: 10.2167/lcc344.0
|View full text |Cite
|
Sign up to set email alerts
|

Basque, Spanish and Immigrant Minority Languages in Basque Schools

Abstract: In the Basque Country there has been a very strong growth in the number of pupils of immigrant origin, the main groups being from Latin America, Europe, Africa, Eastern Europe and Asia. The schooling of these pupils does not follow the same pattern as that of autochthonous pupils, as the immigrants tend to concentrate in state sector schools or in private schools serving students from lower socioeconomic backgrounds. This negative selection is compounded by the tendency of these pupils to concentrate in school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Language ideological debates continue to feature prominently in contemporary societies, with the Catalan independence movement and power sharing in Northern Ireland presenting two such examples where discussions of language rights and claims to legitimacy have taken centre stage. Despite this, research on language learning and immigration in minority language contexts specifically remains on the periphery of academic scholarship (although see Bermingham, 2018;Etxeberrias & Elosegi, 2008;McCubbin, 2010;Pujolar, 2010 for some examples). Multilingualism in European classrooms is now the norm, not exception, and while the management of linguistic diversity is increasingly at the fore of language policy discussions, engagement with the multilingual realities of schools continues to be inadequate, and the linguistic habitus of modern day education systems remains largely monolingual (Busch, 2011;Piller, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language ideological debates continue to feature prominently in contemporary societies, with the Catalan independence movement and power sharing in Northern Ireland presenting two such examples where discussions of language rights and claims to legitimacy have taken centre stage. Despite this, research on language learning and immigration in minority language contexts specifically remains on the periphery of academic scholarship (although see Bermingham, 2018;Etxeberrias & Elosegi, 2008;McCubbin, 2010;Pujolar, 2010 for some examples). Multilingualism in European classrooms is now the norm, not exception, and while the management of linguistic diversity is increasingly at the fore of language policy discussions, engagement with the multilingual realities of schools continues to be inadequate, and the linguistic habitus of modern day education systems remains largely monolingual (Busch, 2011;Piller, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This can be seen especially in the classroom. In Galicia, where this research was conducted, and in the broader Spanish and European contexts, changes in economic structures, coupled with numerous migration waves during the 20th and 21st centuries have led to increasingly linguistically diverse classrooms (Corona et al, 2012;Etxeberrias & Elosegi, 2008;Gkaintartzi & Tsokalidou, 2011;Gkaintartzi et al, 2014;Pulinx et al, 2015;Van Der Wildt et al, 2015). Despite this, the linguistic habitus of the education system remains rooted in monolingualism (Busch, 2013;Piller, 2016), and studies in the Spanish context have demonstrated how linguistic factors can contribute to the poor academic achievement of immigrant students when compared to their local counterparts (Codó & Patiño-Santos, 2014;Patiño-Santos et al, 2015;Pérez-Milans, 2011;Pujolar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Basque education system is structured into three linguistic models: In model A, the instruction is in Spanish and Basque is studied as a subject; in model B, students are instructed both in Spanish and Basque; and in model D, instruction is in Basque and Spanish is studied as a subject. In areas of the BAC where Spanish is the main spoken language in the public sphere, immigrant pupils tend to study model A or 'light' model B, meaning that Basque language instruction is very low (Etxeberria and Elosegi, 2008;Intxausti, Etxeberria and Joaristi 2010;Martínez 2014). By contrast, autochthonous students tend to study model B or D regardless of the area of the BAC in which they are located, in line with Basque language revitalisation efforts.…”
Section: The Studymentioning
confidence: 99%
“…For example, a serious dilemma in the autonomous Basque and Catalonia regions of Spain is how to simultaneously promote the regional NDL and "counterbalance" the high social status of the DL while adequately developing the home NDLs of incoming immigrant learners (Cenoz and Gorter 2012). In the Basque Country, for example, programmes to promote integration of immigrant learners highlight their languages and cultures; a popular one is the Portuguese Language and Culture Programme, which is part of the school curriculum and attracts learners from a range of backgrounds including DL speakers (Cenoz 2009;Etxeberria and Elosegi 2008). Such programmes not only recognize but also celebrate and popularize learners' linguistic and cultural backgrounds, promoting mutual learning, plurilingualism and pluriculturalism.…”
Section: What South and North Can Learn From Each Othermentioning
confidence: 99%